Computational Study of Steel Bracket Connection Subjected To Axial Load - WANG, JEFFREY; KOH HENG BOON, (Recent Trends in Civil Engineering and Built Environment, 2023)
Steel bracket connection is one of the beam-to-column connection enable shear and moment transmit securely from beam to column. This paper presents the finding of the structural behaviour of steel bracket connections with different number of bolts, the arrangement of bolt and unsymmetrical bolt arrangement due to loosen bolts were analysed using LUSAS software. The connections were modelled in 3D. Thick shell element was assigned to the steel column, steel beam and steel plate. The bolts were modelled as the nonlinear thick beam. Nonlinear FEA with material nonlinearity was used to predict the capacity of the steel bracket was increased with the increment of bolts. Meanwhile, structural behaviour and stress distribution of steel bracket connection with loosen bolts are significant different with others and gained lower capacity.